PENGARUH PENGGUNAAN KONTRASEPSI HORMONAL (PIL) TERHADAP PERTUMBUHAN BAYI PADA PERIODE 6 BULAN PERTAMA (UMUR 0-6 BULAN) - , Sri Mujianto, Prof. dr. Siswanto Agus Wilopo, SU, MSc., Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Giving too early complementary feeding effect on the duration of amenorrhea during lactation so that the resumption of postpartum ovulation sooner. Lactation Amenorrhea Method was no longer effective and secure, so be required an effective postpartum contraception and did not interfere the quality of breast milk and infant growth. Objective: To determine the influence of hormonal contraceptive (pills) use on the infants growth in the first 6 months period. Research methods: The non-randomized controlled trials and longitudinal research. Subjects were 6-8 weeks postpartum mothers, 20-35 years old and still breastfeeding. Total sample: 90 respondents, divided into 2 groups, the intervention group and control group. The place of study was in Sleman and Yogyakarta city. Bivariable analysis was using Chi Square, t-test and linear regression. Multivariable analysis was using Linear Regression. Results: Multivariable analysis showed that women taking hormonal contraceptives (pills), the changes in infantâs body weight and body length was 115,96 g higher (R2 = 0,1996% CI = -320,35-552,27) and 0,03 cm lower (R2 = 0,4179 95% CI = -1,04-0,97) than the non-hormonal contraception. Other factors were the variable quality of the milk, the breast milk quantity, breastfeeding status, disease in infants, babies parenting and social insurance/maternity insurance (Jamkesmas /Jampersal) membership. Conclusion: The use of hormonal contraceptives (pills) did not affect the infant's growth in the first 6 months period.